Un par de sandalias - Gaitán, Nery Alexis (Oltreoceano - Rivista sulle migrazioni, 2021)
En esta narrativa, un par de sandalias figura de la falta de recursos, nos acompañan para evidenciar las dificultades que desde la infancia se van resolviendo, parcialmente, con inocencia, dolor y esperanza. La dicha perseguida como constante, en un país incierto, se asoma para compensar a ese ser amado: la madre, que ha dado todo para forjar un futuro digno para sus hijos. A Pair of Sandals In this story, the recurring image of the pair of sandals, which symbolize the lack of resources, sheds light on the difficulties that since childhood are partially resolved with innocence, pain and hope. The happiness constantly pursued as constant, in an uncertain country appears to compensate for the beloved mother who has given everything to forge a decent future for her children.